TINJAUAN PERLINDUNGAN HUKUM PEKERJA RUMAH TANGGA (PRT) DALAM KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) - Rizky Meitha Kumala; Vinsya Murtiningsih (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2013)
AbstractThe purpose of the article is to determine the Legal Protection of Domestic Workers in Cases of Domestic Violence. This article will review the problems are encountered in the work of domestic workers and forms of legal protection given to domestic workers. The problem often faced by Domestic workers are the structural problems of poverty and discrimination; and the problem of working conditions of exploitation, violence, restrictions on freedom and access to information, and there isn’t organization of domestic workers. Legal protection against domestic workers has been relatively good. Legislation can use to protect domestic workers are Constitution of the Republic of Indonesia year 1945; Law No. 23 Year 2004 about the Elimination of Domestic Violence; Law No. 39 Year 1999 about Human Rights; the International Labour Organization Convention (ILO) No. 189 on Decent Work for Domestic Workers. While in Law Number 13 Year 2003 about Manpower Employment is no legal protection against domestic workers. The inhibitory Factors the legal protection of domestic workers are the juridical and social aspects. The law enforcement is expected optimize their role to provide protection and services for victims of domestic violence, one of which is domestic worker.Keywords: Legal Protection; Domestic Workers; Domestic Violence.AbstrakArtikel ini bertujuan untuk mengetahui Perlindungan Hukum Pekerja Rumah Tangga (PRT) dalam Kasus Kekerasan dalam Rumah Tangga (KDRT). Artikel ini akan mengkaji mengenai masalah yang dihadapi PRT dalam menjalankan pekerjaannya dan bentuk perlindungan hukum yang diberikan terhadap PRT. Masalah yang sering dihadapi oleh PRT antara lain adalah masalah struktural yang terdiri dari kemiskinan dan diskriminasi; dan masalah kondisi kerja yang terdiri dari eksploitasi, kekerasan, pembatasan kebebasan dan akses untuk mendapatkan informasi, dan ketiadaan organisasi PRT. Perlindungan hukum terhadap PRT secara umum sudah relative baik. Pengaturan Perlindungan PRT antara lain dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945; Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah tangga; Undang-Undang Nomor 39 Tahun 1999 tentang Hak Asasi Manusia; serta Konvensi Internasional Labour Organization (ILO) Nomor 189 mengenai Kerja Layak Pekerja Rumah Tangga. Sedangkan dalam Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan tidak menjangkau perlindungan hukum terhadap PRT. Faktor-faktor penghambat perlindungan hukum terhadap PRT antara lain meliputi aspek yuridis dan aspek sosial. Diharapkan para aparat penegak hukum dapat mengoptimalkan perannya dalam memberikan perlindungan dan pelayanan bagi korban kekerasan dalam rumah tangga, yang salah satunya adalah PRT.Kata Kunci : Perlindungan Hukum; Pekerja Rumah Tangga (PRT); Kekerasan dalam Rumah Tangga